Analisis Kesulitan Guru PPKn dalam Mengembangkan Materi Pembelajaran Bhinneka Tunggal Ika - Winarno, Winarno Winarno; Rusnaini, Rusnaini; Muchtarom, Moh.; Yuliandri, Erna; Rasyid, Machmud Al; Suryaningsih, Anis (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study aims to identify and analyze the difficulties of junior high school civic education teachers in developing Bhinneka Tunggal Ika (the national slogan unity in diversity) learning materials based on actual issues. The method used is descriptive qualitative. Data was collected using interviews with informants from junior high school civic education teachers in Sukoharjo District and civics field experts, document analysis of civic education (PPKn) textbooks for junior high school and PPKn 2013 curriculum documents, supported by Focus Group Discussions. The results showed that the teacher had no difficulty developing the civic education materials of Bhinneka Tunggal Ika for junior high school because it was based on government textbooks and lesson plans developed by teachers' association (MGMP) of civic education subject for junior high school in Sukoharjo Regency. Difficulties are experienced when presenting actual issues that are close to students' initial experiences related to the materials and the use of instructional technology media that are appropriate to the conditions of the school and students. This is because actual issues that are close to students' initial experiences are not included in the textbook. Likewise, the use of technology to support learning is also not included in textbooks. This makes teachers creatively prepare local, practical and actual issues to support the learning of these materials. The teachers also uses instructional technology media to support learning material by adjusting the conditions of the schools and students. Keywords: civic education subject (PPKn), learning materials, Bhinneka Tunggal Ika ABSTRAK Penelitian ini bertujuan mengidentifikasi dan menganalisis kesulitan guru PPKn SMP dalam mengembangkan materi pembelajaran Bhinneka Tunggal Ika yang berbasis isu aktual. Metode yang digunakan deskriptive kualitatif. Teknik pengumpulan data menggunakan wawancara dengan informan guru PPKn SMP Kabupaten Sukoharjo dan pakar bidang PKn, analisis dokumen terhadap buku ajar PPKn SMP dan dokumen kurikulum PPKn 2013, ditunjang dengan Focus Group Discussion. Hasil penelitian menunjukkan bahwa guru tidak mengalami kesulitan mengembangkan materi aspek Bhinneka Tunggal Ika PPKn SMP dikarenakan sudah mendasarkan pada buku ajar pemerintah dan RPP yang dikembangkan MGMP PPKn SMP Kabupaten Sukoharjo. Kesulitan dialami pada saat menyajikan isu aktual yang dekat dengan pengalaman awal siswa terkait dengan materi dan penggunaan media teknologi pembelajaran yang sesuai dengan kondisi sekolah dan siswa. Hal ini dikarenakan isu aktual dan yang dekat dengan pengalaman awal siswa tidak termuat di buku ajar. Demikian pula, penggunaan teknologi untuk mendukung pembelajaran juga tidak termuat di buku ajar. Hal ini menjadikan guru secara kreatif menyiapkan isu lokal, praktis dan aktual guna mendukung pembelajaran materi tersebut. Guru juga menggunakan media teknologi pembelajaran untuk mendukung pembelajaran materi dengan menyesuaikan kondisi sekolah dan siswa. Kata kunci: Pendidikan Pancasila dan Kewarganegaraan, materi pembelajaran, Bhinneka Tunggal Ika